The Feature of Female Language in the Novel Love Rosie - Yushi Aprindah Putri; Muhammad Adam; Siti Hafsah (Prologue: Journal on Language and Literature, 2020)
This journal investigated the feature of female language in the Novel entitled Love Rosie. There are two objectives of this research; 1) to identify the type of feature female language used by the main character in the novel Love Rosie and 2) to describe which female language feature supports the communication style. The type of research was qualitative descriptive because the data were analyzed and described in the form of words and sentences. The data were taken from the conversations that is uttered by the main character of Love Rosie the novel. The conversation in the novel was taken out as the primary data. The theory used in this research is the sociolinguistics analysis using Robin Lakoff's theory of female language feature and supported by Deborah Tannen's theory of communication styles in women's conversation. The result of the research, the researcher found that the features of female language found in the novel Love Rosie there are eight types, super polite forms, tag questions, empty adjectives, logical hedges, strong avoidance of words, price color terms, intensifiers, and emphatic stress. The female language feature that is the most widely used main character supports the communication style that tends to use indirect communication styles.